2019
DOI: 10.1101/553537
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospital use of antibiotics as the main driver of infections with antibiotic-resistant bacteria – a reanalysis of recent data from the European Union

Abstract: Antimicrobial resistance in bacteria causes significant morbidity worldwide. The development and acquisition of resistance to antibiotics is believed to primarily develop under the selective pressure of widespread antibiotic use in humans, however antimicrobial usage in livestock has been proposed as additional, if not principal, driver of antibiotic resistance. In this work, we correlate recent data from the European Union on antibiotic resistance rates with data on antibiotic usage in the primary care and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…As many of the studies we found were hospital-based our results support the need for resources and policies for control of nosocomial infection. A recently published modelling study showed that antibiotic use in hospital is a major driver for antimicrobial resistance in human infection compared with animal and environmental antibiotic exposures 65 . Although infection control and hygiene may be sub-optimal in the countries we studied, infection control is easier to manage within health-care institutions than in other unstructured systems such as animal husbandry and the environment.…”
Section: Discussionmentioning
confidence: 90%
“…As many of the studies we found were hospital-based our results support the need for resources and policies for control of nosocomial infection. A recently published modelling study showed that antibiotic use in hospital is a major driver for antimicrobial resistance in human infection compared with animal and environmental antibiotic exposures 65 . Although infection control and hygiene may be sub-optimal in the countries we studied, infection control is easier to manage within health-care institutions than in other unstructured systems such as animal husbandry and the environment.…”
Section: Discussionmentioning
confidence: 90%
“…The global epidemic of antibiotic resistance and associated infections has put hospitals at the epicenter of this challenge 1 . It is estimated that if the spread of antibiotic resistance grows unchecked, it will cause millions of deaths worldwide, with a concomitant economic impact of >100 trillion dollars by 2050 2 .…”
Section: Introductionmentioning
confidence: 99%
“…he global epidemic of antibiotic resistance has refocused attention on infection prevention and control in hospitals 1 . It is estimated that if the spread of antibiotic resistance grows unchecked, it will cause millions of deaths worldwide, with an economic impact of more than US$100 trillion by 2050 (ref.…”
mentioning
confidence: 99%